Implementation and Results of a New Problem Solving Approach in Physics Teaching - Ince, Elif (Momentum: Physics Education Journal, 2019)
Teaching problem solving is one of the most important topics of physics education while students have big troubles with physics problem solving. The aim of this research is to investigate the impact of extended problem-solving strategy instruction on the development of pre-service science teacherÃ¢â‚¬â„¢s problem-solving, critical thinking, metacognitive awareness, and logical reasoning skills. Extended Problem-Solving Strategy has been developed for university physics courses by researcher. This strategy has importantance in terms of covering many previous strategies in physics education literature and including many new steps. The model of the research consisted of an experimental design with pre-test and post-test control groups. Pre-services randomly assigned to the experimental (N=30) and control groups (N=30). The results of the research indicate that the post scores of the experimental group students significantly higher than control group students after the implementations in terms of metacognitive awareness, critical thinking, problem solving and logical thinking skills.This research revealed the positive effects of the Ã¢â‚¬Å“Extended Problem-Solving StrategyÃ¢â‚¬Â implementation in the physics course at the university level on the skills which are listed among the 21st Century skills and each of these skills affects the other skills positively